Wheat Variety-Specific Response to Seeding Rate Under Intensive Management Conditions in Western Kansas in 2020–2021 - R. P. Lollato; N. Giordano; L. Ryan; L. M. Simão; J. R. Soler; L. O. Pradella (Kansas Agricultural Experiment Station Research Reports, 2022)
Wheat response to seeding rate is variable and depends on resource availability during the growing season (e.g., fertility, moisture, and temperature). Our objective was to evaluate winter wheat population and grain yield responses to seeding rate and its interaction with variety in a highly-managed production system where manageable stresses were limited. This study was established to evaluate the response of the wheat varieties Joe, WB-Grainfield, Langin, and LCS Revere to five seeding rates ranging from 200,000 to 1,000,000 seeds per acre. The site was managed by growers that consistently win state and national wheat yield contests near Leoti, KS. The trial was established on September 25, 2020, after a long summer fallow in sorghum residue, approximately 10 days after a 0.3-in. rainfall event, ensuring good stand establishment. The fall was dry, but spring conditions were favorable for high yields with cool temperatures and about 11 inches of precipitation. There were significant effects of seeding rate and variety on stand count, but the interaction was weak (P = 0.12). Main effects suggested that the stand count increased with increases in the seeding rate (from 252,265 to 521,347 plants per acre), with the 800,000 and 1,000,000 seeds/a rates attaining the highest stands. However, we note that final populations were closer to the target population at lower seeding rates as compared to higher seeding rates. Grain yield also depended primarily on variety and on seeding rate, with no interaction between both effects. Grain yield ranged between 97 and 101.3 bushels per acre for the seeding rates ranging between 600,000 and 1,000,000, and from 89.9 to 93.3 bu/a for lower seeding rates. Langin was the highest yielding variety (102 bu/a), followed by LCS Revere and WB-Grainfield (94.7–97.5 bu/a), and lastly by Joe (90.3 bu/a). These results suggest that wheat grain yield responses to seeding rate were not dependent on variety, with optimum seeding rates as low as 600,000 seeds/a. We note that increasing seeding rates beyond 600,000 seeds/a led to numerical but not statistical increases in yield.
Keywords: population; yield potential; variety; wheat; seeding rate; intensive management; crop density; yield contest